Tailoring of carbon-encapsulated nickel nanoparticles/biochars for efficient degradation of tetracycline - Guo, Yi; Wang, Rong (Frontiers in Materials, 2025)
As excellent peroxydisulfate (PDS) activators to degrade antibiotics, metallic nanoparticles (NPs) suffer from continuous ion leakage and declined efficiency. Herein, graphene coated nickel (Ni@G) NPs with 23.9–28.5 nm of Ni core and 7.9–2.1 layers of graphene shell were regulated via laser ablation in ammonia solution. Ni@G-loaded biochars (Ni@G/Bs) with developed porosity (23.8–145.7 m2/g) were prepared via crosslinking Ni@G with biochars derived from the pyrolysis of rice hull at 300 °C, 450 °C and 600 °C. By investigating the effects of catalyst species and dosage, PDS dosage, tetracycline concentration, circumstance temperature and coexisting anions, Ni@G/Bs presented k values of 0.0094–0.0301 min−1 for tetracycline degradation which were 47.0–81.5 fold enhancement than biochars. 7.26–3.61 μg/L of nickel ion leakage for 1st-5th cycles verified the excellent stability of Ni@G/Bs. Paracetamol (72.4%), ciprofloxacin (76.7%) and aureomycin (68.2%) could be degraded, showing a superior versatility of Ni@G/Bs. Free radical degradation pathway involving •OH, •SO4− and •O2− governed the degradation mechanism. While the non-free radical pathway mediated by 1O2 should not be ignored. This study paved a way for adjusting laser-ablated core/shell NPs and provided a new insight for integrating metal NPs and biochars to efficiently degrade antibiotics.